Catalytic and Chemoselective Oxidation of Activated Alcohols and Direct Conversion of Diols to Lactones with In Situ‐Generated Bis‐IBX Catalyst1. Issue 12 (7th March 2013) - Seth, Saona; Jhulki, Samik; Moorthy, Jarugu Narasimha
Abstract: The twisted 3, 3′‐diiodo‐2, 2′, 6, 6′‐tetramethoxybiphenyl‐4, 4′‐dicarboxylic acid (DIDA ) was designed and synthesized for the in situ generation ofBis‐IBX and catalytic oxidations. The seemingly better solubility of the in situ‐generatedBis‐IBX and the attenuated reactivity arising from its unique structural features and methoxy substituents allowed the catalytic oxidation of activated alcohols selectively usingDIDA /oxone. Chemoselective oxidations were demonstrated for substrates containing two different hydroxy groups. Furthermore, the unique reactivity ofDIDA was demonstrated for sequential oxidation reactions of 1, 4‐ and 1, 6‐diols to give lactones catalytically in respectable yields. Abstract : The twisted 3, 3′‐diiodo‐2, 2′, 6, 6′‐tetramethoxybiphenyl‐4, 4′‐dicarboxylic acid (DIDA ), used catalytically, permits the in situ generation of aBis‐IBX, and promotes the chemoselective oxidation of activated alcohols.